Housing insecurity and sleep among welfare recipients in California. Issue 7 (1st February 2021) - Bozick, Robert; Troxel, Wendy M; Karoly, Lynn A
Abstract: Study Objectives: To estimate the effect of housing insecurity on sleep duration and sleep quality. Methods: Using longitudinal data from a sample of 1, 046 welfare recipients in the state of California followed from 2015–2016 through 2017–2018, we regressed self-reported measures of sleep duration and sleep quality recorded in 2017–2018 on experiences of housing insecurity in the prior year. We applied propensity score weights to attenuate potential bias from an array of observed covariates, including sleep duration and sleep quality measured prior to experiences with housing insecurity. Results: Sample members who were unable to make their rent/mortgage payments slept on average 22 fewer minutes a night and had lower quality sleep than those who were able to make their rent/mortgage payments. Sample members who were forced to move because of an inability to make rent/mortgage payments slept on average 32 fewer minutes a night and had lower quality sleep than those who were not forced to move. Conclusions: By compromising sleep health, housing insecurity represents a distinct form of stress in the lives of economically-disadvantaged adults, which could also contribute to other health disparities.